Preparation method and application of nitrogen-doped metal nanocluster ball-milled straw biochar catalyst
Through the preparation method of nitrogen-doped metal nanocluster ball milling straw biochar catalyst, the problems of poor stability and limited activity of traditional catalysts are solved, and efficient, stable and environmentally friendly water pollutant treatment effect is achieved.
Patent Information
- Application Number
- CN202510050842.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-29
AI Technical Summary
Traditional non-metal doped biochar catalysts have problems such as poor stability, short lifetime and limited activity, and metal doped catalysts face the risks of chemical inertia and metal oozing when improving catalytic activity.
The preparation method of nitrogen-doped metal nanocluster ball milling straw biochar catalyst is used to prepare a catalyst with high catalytic efficiency and stability by ball milling crop straw with spherical zirconia, and then uniformly mixing and annealing with metal compounds and nitrogen source substances.
It realizes the efficient degradation of organic pollutants by catalysts, has high stability, long life and high specific surface area, avoids metal ions leakage, and is suitable for pollutant treatment of various water bodies.
Smart Images

Figure CN119897139A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation and sewage treatment, and specifically relates to a preparation method and application of a nitrogen-doped metal nanocluster ball-milled straw biochar catalyst. Background Art
[0002] As a major agricultural country, my country has extremely rich straw resources, accounting for one-fifth of the global straw production. However, traditional straw processing methods, such as burning, not only cause environmental pollution, but also lead to resource waste. Therefore, using straw to prepare biochar not only helps solve environmental problems, but can also be used for carbon capture and storage, thereby alleviating the global warming problem caused by CO emissions during traditional processing.
[0003] Crop straw is mainly composed of cellulose, hemicellulose and lignin, rich in active functional groups such as hydroxyl, carboxyl and peptide chains, which can directly react with some pollutant ions in water bodies and have excellent chemical modification potential. However, traditional biochar materials prepared with raw crop straw as precursors, although showing certain catalytic ability, often make it difficult to increase the types and number of active sites of the materials due to the complex composition of biomass raw materials, which leads to low efficiency of activated oxidants. In addition, biochar catalysts are easily deactivated by various environmental factors such as coexisting organic pollutants, inorganic anions, pH value, etc., and the small molecular organic matter produced in the catalytic degradation reaction is easy to block the internal pores of the material and shield the active sites.
[0004] Although traditional non-metal-doped biochar catalysts have advantages such as environmental protection, high chemical activity and significant cost-effectiveness, they face challenges such as poor stability, short life and limited activity. Although metal doping can improve catalytic activity to a certain extent, the chemical inertness of the original carbon material has become a bottleneck for improving catalytic performance. The catalytic efficiency needs to be improved, and there is a potential risk of metal leakage.
[0005] The application of catalysts in wastewater treatment is generally combined with wastewater treatment processes. Chinese patent document CN110407368 A (application number: 201910797677.5) discloses a deep defluorination treatment process and defluorination treatment system for low-concentration fluorine-containing wastewater. In the prior art, there is no report on the degradation of organic matter in wastewater using the deep defluorination treatment process for low-concentration fluorine-containing wastewater disclosed in the patent document combined with a biochar catalyst. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a method for preparing a nitrogen-doped metal nanocluster ball-milled straw biochar catalyst and its application.
[0007] The preparation method provided by the present invention simplifies the preparation process of metal-doped catalysts and reduces the preparation cost of catalyst materials. The nitrogen-doped metal nanocluster ball-milled straw biochar catalyst (M-BNC) prepared by the present invention has the advantages of high catalytic efficiency, high stability, long life and high specific surface area, and also avoids problems such as metal ion leakage. It is suitable for various water bodies and effectively solves the problems of poor stability, short life, limited activity and the like faced by traditional non-metal-doped biochar catalysts.
[0008] The technical solution of the present invention is as follows:
[0009] A method for preparing nitrogen-doped metal nanocluster ball-milled straw biochar catalyst comprises the following steps:
[0010] S1, washing, drying, crushing and sieving crop straw to obtain straw powder;
[0011] S2, the straw powder prepared in S1 and spherical zirconium oxide are ball-milled to obtain a powder which is labeled as B-Straw;
[0012] S3, adding the B-Straw powder prepared in S2 to a mixed solution of a metal compound and Zn(NO3)2·6H2O, stirring the solution for 0.2-4.0 hours, allowing it to stand for aging, and then separating the solid from the liquid to obtain a solid as a precursor;
[0013] The metal compound includes any one of NiCl2·6H2O, Co(NO3)2·6H2O, Fe(NO3)3·9H2O, and MnCl2·4H2O;
[0014] S4, uniformly mixing the precursor obtained in S3 with 5-25 times the weight of a nitrogen source substance, and annealing the mixed powder in a nitrogen atmosphere at a flow rate of 10-100 mL / min;
[0015] The nitrogen source substance includes any one of dicyandiamide, melamine and urea;
[0016] S5. The product obtained in S4 is acid-washed, dried and sieved to obtain a nitrogen-doped metal nanocluster ball-milled straw biochar catalyst.
[0017] Preferably, according to the present invention, in step S1, impurities on the surface of the crop straw are removed by washing with pure water.
[0018] Preferably according to the present invention, in step S1, the crop straw is dried at 40-80°C.
[0019] Preferably according to the present invention, in step S1, the screening is performed by filtering through a 30-50 mesh screen.
[0020] Preferably according to the present invention, in step S1, the crop straw includes any one or more of wheat straw, corn straw, rice straw and cotton straw.
[0021] Preferably, in step S2, the diameters of the spherical zirconia are 4-7 mm and 8-12 mm, the weight ratio of the two diameters is (3-5):1, and the mass ratio of the spherical zirconia to the crop straw is (50-150):1;
[0022] Further preferably, the mass ratio of spherical zirconia to crop straw is 100:1.
[0023] Preferably, according to the present invention, in step S2, the straw powder is placed in a ball mill container and then ground at a speed of 300-500 rpm / min for 3-8 hours, with the rotation direction being changed every 0.5-1 hour.
[0024] Preferably, according to the present invention, in step S3, the mass volume ratio of the mixed solution of B-Straw powder, metal compound and Zn(NO3)2·6H2O is (1-10): 500 g / mL;
[0025] In the mixed solution of the metal compound and Zn(NO3)2·6H2O, the concentration of the metal compound is 10-50 mM, and the concentration of Zn(NO3)2·6H2O is 50-200 mM;
[0026] The mixture is allowed to stand for aging for 5-24 hours; the precursor is separated by suction filtration and dried at 40-80°C.
[0027] Preferably according to the present invention, in step S4, the precursor is uniformly mixed with 8-12 times the weight of the nitrogen source material.
[0028] Preferably according to the present invention, in step S4, the precursor and the nitrogen source material are uniformly mixed by grinding.
[0029] Preferably according to the present invention, in step S4, the mixed powder is annealed in a tube furnace under a nitrogen atmosphere at a flow rate of 10-100 mL / min.
[0030] Preferably, according to the present invention, in step S4, the mixed powder is annealed in a nitrogen atmosphere with a flow rate of 40-60 mL / min, the temperature is increased from room temperature to 500-600°C at a rate of 5°C / min, and the temperature is kept constant for 1-2 hours, and then the temperature is increased to 850-950°C at a rate of 3°C / min, and the temperature is kept constant for 1-2 hours.
[0031] Preferably, according to the present invention, in step S5, the product obtained in S4 is washed with hydrochloric acid and then dried, and then ground and sieved to obtain a nitrogen-doped metal nanocluster ball-milled straw biochar catalyst.
[0032] Further preferably, the hydrochloric acid concentration is 0.5-2 mol / L, and after stirring and soaking for 2-6 hours, it is washed with pure water until neutral; after grinding, it is passed through a 50-200 mesh sieve.
[0033] A nitrogen-doped metal nanocluster ball-milled straw biochar catalyst is prepared according to the method.
[0034] The nitrogen-doped metal nanocluster ball-milled straw biochar catalyst prepared by the above method is used in the oxidative degradation of organic pollutants in wastewater treatment.
[0035] Preferably, according to the present invention, the nitrogen-doped metal nanocluster ball-milled straw biochar catalyst prepared by the above method is used in catalytic oxidant degradation of organic pollutants in wastewater.
[0036] Further preferably, the oxidant includes one or more of sodium persulfate, potassium persulfate, potassium hydrogen persulfate, sodium peroxydisulfate, and potassium periodate.
[0037] More preferably, the organic pollutants include one or more of p-nitrophenol, bisphenol A, oxytetracycline, ciprofloxacin, and phenytoin.
[0038] Preferably, the specific method of the above application comprises the following steps:
[0039] The nitrogen-doped metal nanocluster ball-milled straw biochar catalyst and one or more of sodium persulfate, potassium persulfate, potassium hydrogen persulfate, sodium peroxydisulfate, and potassium periodate are put into the wastewater containing organic pollutants with a pH of 3.8-10 and deep treatment, at a temperature of 15-40°C, and continuously stirred until the organic pollutants are degraded.
[0040] Further preferably, the deep treatment method for the wastewater is a deep defluorination treatment process for low-concentration fluorine-containing wastewater.
[0041] The beneficial effects of the present invention include at least the following:
[0042] The nitrogen-doped metal nanocluster ball-milled straw biochar catalyst prepared by the present invention realizes the uniform dispersion of metal nanoclusters on the biochar carrier, and significantly improves the reaction performance and water treatment efficiency of the catalyst by constructing a metal-nitrogen-carbon structure. Compared with conventional metal catalysts, the M-BNC catalyst has better stability and reusability. The synergistic effect between its carbon, metal and nitrogen components enhances the reaction efficiency of the active sites, while reducing the amount of metal used and the risk of environmental pollution.
[0043] At the same time, the metal in the M-BNC catalyst exists in the form of nanoscale size, which stimulates greater metal activity. At the same time, its rich pore structure and high specific surface area further enhance the catalytic efficiency. Compared with traditional catalysts, the metal nanoclusters in M-BNC exhibit excellent catalytic performance, maximize the utilization of metal atomic sites, and significantly enhance the ability to activate peroxymonosulfate (PMS), thereby achieving a significant increase in catalytic efficiency and a significant reduction in manufacturing costs. In addition, the M-BNC catalyst combines the advantages of metal and non-metal doping, has rich active sites, stable material structure and extremely low metal leakage risk, ensuring the environmental friendliness of the material. At the same time, it is easy to separate from the reaction system and is easy to recycle, further improving the economy and practicality of the catalyst material. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 A schematic diagram of a method for preparing a nitrogen-doped metal nanocluster ball-milled straw biochar catalyst provided by the present invention (taking Ni compounds as an example).
[0045] Figure 2 The SEM images of original wheat straw and ball-milled straw;
[0046] In the figure: (a) is the SEM image of original wheat straw, and (b) is the SEM image of ball-milled straw.
[0047] Figure 3 This is the SEM image of ball-milled nitrogen-doped straw biochar.
[0048] Figure 4 This is a SEM image of Ni / 24-BNC prepared in Example 1 of the present invention.
[0049] Figure 5 This is a test image of Ni / 24-BNC obtained in Example 1 of the present invention;
[0050] In the figure: (a) and (b) are transmission electron microscopy (TEM) morphology images of Ni / 24-BNC; (c) spherical aberration corrected high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) morphology image; (d) corresponding X-ray energy spectrum (EDS) image of C, N, and Ni elements.
[0051] Figure 6 This is the X-ray powder diffraction (XRD) spectrum of Ni / 24-BNC prepared in Example 1 of the present invention.
[0052] Figure 7 This is a graph showing the effect of different Ni loading amounts on the catalytic activity of the nitrogen-doped Ni nanocluster ball-milled straw biochar catalyst prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0053] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.
[0054] The contents not described in detail in the embodiments are based on the prior art in the art.
[0055] The equipment models used in the examples are shown in Table 1.
[0056] Table 1
[0057]
[0058] Figure 1 A schematic diagram of a method for preparing a nitrogen-doped metal nanocluster ball-milled straw biochar catalyst provided by the present invention (taking Ni compounds as an example).
[0059] The experimental method for the degradation of p-nitrophenol (PNP) organic matter by nitrogen-doped metal nanocluster ball-milled straw biochar catalyst includes the following steps:
[0060] 100 ml of deionized water was measured in a 200 ml beaker, 2 mg of PNP was weighed and added to the beaker, ultrasonicated for 30 min and stirred for 30 min to fully dissolve the PNP pollutant, and then the C0 value was tested in a UV-5100 ultraviolet spectrophotometer, PMS (potassium persulfate purchased from Shandong Keyuan Biochemical Co., Ltd.) was weighed to a final concentration of 3 mM and 0.02 g of Ni / 24-BNC catalyst was added to the beaker at the same time and the timing was started. The degradation experiment was carried out under magnetic stirring at 180 rpm. At fixed time intervals (2, 4, 6, 8, 10, 20, 30 min), about 2 ml of the reacted solution was extracted with a 5 ml syringe, and after filtering through a 0.22 μm filter head, the absorbance of PNP was immediately detected with a UV-5100 ultraviolet spectrophotometer C t value, set the wavelength to 314nm. Use the Excel spreadsheet to calculate C t / C0, and then calculate the average C of the parallel samples t / C0, using the formula (1-C t / C0)×100% to get its removal rate. In the above experiment, the PNP concentration was 20 mg / L, the PMS concentration was 3 mM and the catalyst concentration was 0.2 g / L.
[0061] Example 1
[0062] This example prepares a nitrogen-doped nickel nanocluster ball-milled straw biochar catalyst, including the following preparation steps:
[0063] S1. Preparation of straw powder: Wash the wheat straw with pure water to remove surface impurities, dry it in a DHG-9213A oven at 80°C overnight until dry, grind it in a mortar and filter it through a 40-mesh sieve to prepare wheat straw powder;
[0064] S2, preparation of wheat straw precursor (B-Straw): 1.5g of straw powder prepared in step S1, spherical zirconium oxide with diameters of 6mm and 10mm, the weight ratio of the two diameters of 6mm and 10mm being 4:1, were ground in a 100mL zirconium oxide container. The ball-powder mass ratio was 100:1, and the grinding was carried out at a speed of 450rpm / min for 5h, and the rotation direction was changed once every 0.5h, and the straw powder was marked as B-Straw;
[0065] B-Straw powder was prepared according to the above method and the experimental dosage.
[0066] S3, 4g of B-Straw powder prepared in step S2, 2.85g of NiCl2·6H2O (to a final concentration of 24mM) and 14.28g of Zn(NO3)2·6H2O (to a final concentration of 96mM) were dissolved in 500ml of deionized water, and the solution was stirred at a constant speed for 1h to mix the metal ions and the straw evenly. After standing and aging for 10h, the Ni-BNC precursor was separated by suction filtration and dried at 80°C for 12h until dry.
[0067] S4. The precursor obtained in step S3 and 10 times the weight of dicyandiamide are ground and evenly mixed in a mortar. The mixed powder is step-annealed in an OTL1200 tube furnace in a nitrogen atmosphere with a flow rate of 50 mL / min. The temperature is increased from room temperature to 550° C. at a rate of 5° C. / min, and maintained at this temperature for 1 hour. Then, the temperature is increased to 900° C. at a rate of 3° C. / min, and maintained at this temperature for 1 hour.
[0068] S5. The product obtained after cooling the tube furnace was taken out and stirred and soaked in 1 mol / L hydrochloric acid for 4 hours, then washed with pure water until the pH was neutral and dried in an oven. Then, the product was ground in a mortar and filtered through a 100-mesh screen to prepare a nitrogen-doped nickel nanocluster ball-milled straw biochar catalyst (Ni / 24-BNC catalyst).
[0069] The prepared nitrogen-doped metal nickel nanocluster ball-milled straw biochar catalyst was characterized, and the morphologies of the original straw (wheat straw powder prepared in the above step S1), ball-milled straw (B-Straw powder prepared in the above step S2), ball-milled nitrogen-doped straw biochar (the same as the ball-milled nitrogen-doped straw biochar in Table 4 below) and Ni / 24-BNC catalyst were characterized by SEM and HAADF-STEM. Figure 2 The SEM images of original wheat straw and ball-milled straw; Figure 3 is the SEM characterization of ball-milled nitrogen-doped biochar, Figure 4 SEM characterization of nitrogen-doped nickel nanocluster ball-milled straw biochar catalyst (Ni / 24-BNC). Figure 3 and Figure 4 By comparison, it can be seen that the metal-doped biochar is more fluffy, has a larger specific surface area and pore size, and is more conducive to adsorption and catalytic reactions. Figure 5 The spatial position of metal atoms is further revealed. Figure 5 (a) and (b) are transmission electron microscopy (TEM) morphology images of Ni / 24-BNC; (c) is a spherical aberration-corrected high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) morphology image; Figure 5 As shown in (d), C, N and Ni on the Ni / 24-BNC catalytic material are evenly distributed, and the isolated bright spots in the figure can be attributed to nanoclusters, confirming the high dispersion of metal atoms in the entire Ni / 24-BNC catalyst structure. Figure 6 As shown, the results show that Ni / 24-BNC has only an obvious (002) graphite carbon diffraction peak at 26.2°, and no diffraction peak of metallic Ni, which can further confirm that Ni is loaded on the carbon material in the form of highly dispersed nanoclusters.
[0070] Example 2
[0071] The difference between Example 2 and Example 1 is that in step S2, the mass ratio of straw powder and spherical zirconia ground in a 100 mL zirconia container is different, and the other steps are the same as Example 1, which will not be repeated here. The setting of the mass ratio of straw powder to spherical zirconia in Example 2 is shown in Table 2. The results show that the catalytic performance of the nitrogen-doped nickel nanocluster ball-milled straw biochar catalyst is significantly affected by the mass ratio of wheat straw to spherical zirconia balls. When the ball-to-material mass ratio is 100:1, the catalytic rate of biochar is the highest.
[0072] The experimental method for the catalyst degradation of p-nitrophenol (PNP) organic matter refers to the above experimental method.
[0073] Table 2 Setting of ball-to-material mass ratio in Example 2 and catalytic efficiency of the obtained catalyst biochar
[0074]
[0075] Example 3
[0076] The difference between Example 3 and Example 1 is that in step S4, the mass ratio of the precursor to dicyandiamide is different, and the other steps are the same as Example 1, which will not be repeated here. The setting of the mass ratio of Ni-BNC precursor to dicyandiamide in Example 3 is shown in Table 3. The results show that when the optimal mass ratio of dicyandiamide to wheat straw precursor is 10:1, the biochar catalytic rate is the best.
[0077] The experimental method for the catalyst degradation of p-nitrophenol (PNP) organic matter refers to the above experimental method.
[0078] Table 3 Setting of mass ratio of dicyandiamide to precursor and catalytic efficiency of biochar obtained
[0079]
[0080] Example 4
[0081] The difference between Example 4 and Example 1 is that in step S3, the nickel content in the Ni-BNC precursor is different. The other steps are basically the same as Example 1 and will not be repeated here. In Example 4, three nickel dosages are set to prepare the catalyst, that is, 16mM, 24mM and 32mM NiCl2·6H2O are added respectively, and finally Ni / 16-BNC, Ni / 24-BNC and Ni / 32-BNC are prepared. Figure 7 The results show that the degradation rate of PNP by activating PMS with Ni / 24-BNC catalyst is the best. The experimental method for the degradation of p-nitrophenol (PNP) organic matter by catalyst is based on the above experimental method.
[0082] Figure 7 NC is the nitrogen-doped biochar in Table 4, B-NC is the ball-milled nitrogen-doped straw biochar in Table 4, and Ni / 24-NC is the metal nitrogen-doped unmilled straw biochar.
[0083] Example 5
[0084] The difference between Example 5 and Example 1 is that in step S3, the prepared B-Straw powder is dissolved in a different metal solution, and the other steps are basically the same as Example 1, which will not be repeated here. The three solutions set in Example 5 are Co(NO3)2·6H2O, MnCl2·4H2O, and Fe(NO3)3·9H2O (all with a concentration of 24mM) respectively mixed with 96mM Zn(NO3)2·6H2O to obtain the solution.
[0085] The experimental method for the degradation of p-nitrophenol (PNP) organic matter by catalysts refers to the above experimental method. The results show that when the pollutant concentration is 20 mg / L, the catalyst material doped with metal Ni has a better catalytic effect than the catalyst doped with other metals. Among them, the Ni-BNC (Ni / 24-BNC) catalyst increased the removal efficiency of PNP from 31.8% to 95.8% compared with nitrogen-doped biochar, an increase of 64%. Compared with unmilled nickel-nitrogen co-doped straw, the removal efficiency of PNP by Ni-BNC catalyst increased from 54.8% to 95.8%, an increase of 41%. Compared with unmilled Co-nitrogen co-doped straw, the removal efficiency of PNP by Co-BNC catalyst increased from 53.9% to 83.8%, an increase of 29.9%. Compared with unmilled Fe-nitrogen co-doped straw, the removal efficiency of PNP by Fe-BNC catalyst increased from 51.0% to 74.6%, an increase of 23.6%. Compared with the unmilled Mn-N co-doped straw, the removal efficiency of PNP by Mn-BNC catalyst increased from 45.5% to 65.8%, an increase of 20.3%, as shown in Table 4.
[0086] Nitrogen-doped biochar catalyst: Compared with the catalyst prepared in Example 1, the ball milling step is omitted and no metal oxide is added; specifically, the wheat straw powder prepared in step S1 is used as a precursor to carry out steps S4 and S5 to obtain nitrogen-doped biochar.
[0087] Ball-milled nitrogen-doped straw biochar: Compared with the catalyst prepared in Example 1, no metal oxide is added; specifically, the B-Straw powder prepared in step S2 is used as a precursor to carry out steps S4 and S5 to obtain ball-milled nitrogen-doped straw biochar.
[0088] Metal nitrogen-doped unmilled straw biochar: Compared with the catalyst prepared in Example 1, the ball milling step is omitted; specifically, the wheat straw powder prepared in step S1 is used as a precursor to carry out steps S3, S4 and S5 to obtain metal nitrogen-doped unmilled straw biochar.
[0089] Table 4 Treatment efficiency of pollutants by metal nanoclusters of different element types in Example 5
[0090]
[0091] Example 6
[0092] The Ni / 24-BNC catalyst prepared in Example 1 was selected to carry out cyclic stability experiments, actual water application, and water chemical conditions to verify the stability and adaptability of the catalyst.
[0093] Cyclic stability experiment: After catalytic degradation of PNP using the above experimental method, the solution after the reaction was centrifuged for 3 minutes at a speed of 8000r / min, the supernatant was poured off, the remaining solid material was recovered, washed with distilled water 3 times, washed with anhydrous ethanol 3 times, and then dried in an oven at 60°C and reused in subsequent PNP degradation tests. The experimental results show that after the second cycle, Ni / 24-BNC still maintains a high PNP removal rate of 87.5%; in the third cycle, the removal rate can still be maintained at about 80%, so the Ni / 24-BNC catalyst shows good cyclic stability.
[0094] Application in actual water bodies: When the catalyst is applied to various water bodies that are closer to the actual situation, the Ni / 24-BNC / PMS system also shows significant treatment efficiency. When tap water, Daming Lake water, and secondary sedimentation tank effluent (Plant 1 of Guangshui Water Co., Ltd.) are used to replace the deionized water in the above experimental method for degrading p-nitrophenol (PNP) organic matter, Ni / 24-BNC can maintain excellent degradation efficiency, with PNP removal rates of 91.1%, 92.6%, and 89.2%, respectively. This result not only illustrates the wide applicability of the Ni / 24-BNC catalyst, but also highlights its potential to effectively remove pollutants under complex and changeable actual water quality conditions.
[0095] Application of deep treatment: Ni / 24-BNC catalyst was applied to the effluent of the secondary sedimentation tank treated by the deep defluorination treatment process for low-concentration fluorine-containing wastewater disclosed in Chinese patent document CN201910797677A (application number: 201910797677.5). The effluent of the secondary sedimentation tank was used instead of the deionized water in the above experimental method for degrading p-nitrophenol (PNP) organic matter. The Ni / 24-BNC catalyst showed an improvement in treatment efficiency, with the removal rate increased from 89.2% to 93.5%; the result was better than the direct treatment of the effluent of the secondary sedimentation tank of the sewage treatment plant. This result shows that under the complex and changeable real water quality conditions, the deep defluorination treatment process for low-concentration fluorine-containing wastewater disclosed in Chinese patent document CN201910797677A (application number: 201910797677.5) is used as a pretreatment for catalytic oxidation of the Ni / 24-BNC / PMS system, which is obviously beneficial to the improvement of pollutant treatment efficiency.
[0096] Water chemical condition experiment: Adjust the solution pH and add coexisting anions to verify the adaptability of the catalyst in water. When the initial pH value is set at 3, 5, 7, 9 and 11, the removal rate of PNP reaches 86.6%, 91.6%, 94.8%, 87.8% and 86.6%, respectively. In a wide pH range, the Ni / 24-BNC / PMS system can maintain the ability to efficiently remove PNP. The Ni / 24-BNC catalyst can adapt to a wide range of acid and base environments.
[0097] When exploring the anti-interference ability of the Ni / 24-BNC / PMS system for coexisting anions, chloride ions (NaCl), bicarbonate ions (NaHCO3), nitrate ions (NaNO3) and dihydrogen phosphate ions (NaH2PO4) were introduced, and the concentration of each ion was 10mmol·L-1. The results showed that under the influence of these coexisting anions, the removal rates of PNP reached 88.1%, 92.5%, 85.1% and 86.1%, respectively, which shows that the Ni / 24-BNC / PMS system has greater anti-interference ability.
[0098] The nitrogen-doped metal nanocluster ball-milled straw biochar catalyst prepared by the present invention achieves uniform dispersion of metal nanoclusters on the biochar carrier, and significantly improves the reaction performance and water treatment efficiency of the catalyst through the construction of a metal-nitrogen-carbon structure. It has the advantages of high catalytic efficiency, high stability, long life and high specific surface area.
Claims
1. A method for preparing nitrogen-doped metal nanocluster ball-milled straw biochar catalyst, characterized in that: The steps include: S1, washing, drying, crushing and sieving crop straw to obtain straw powder; S2, the straw powder prepared in S1 and spherical zirconium oxide are ball-milled to obtain a powder which is labeled as B-Straw; S3, adding the B-Straw powder prepared in S2 to a mixed solution of a metal compound and Zn(NO3)2·6H2O, stirring the solution for 0.2-4.0 hours, allowing it to stand for aging, and then separating the solid from the liquid to obtain a solid as a precursor; The metal compound includes any one of NiCl2·6H2O, Co(NO3)2·6H2O, Fe(NO3)3·9H2O, and MnCl2·4H2O; S4, uniformly mixing the precursor obtained in S3 with 5-25 times the weight of a nitrogen source substance, and annealing the mixed powder in a nitrogen atmosphere at a flow rate of 10-100 mL / min; The nitrogen source substance includes any one of dicyandiamide, melamine and urea; S5. The product obtained in S4 is acid-washed, dried and sieved to obtain a nitrogen-doped metal nanocluster ball-milled straw biochar catalyst.
2. The method according to claim 1, characterized in that In step S1, the impurities on the surface of the crop straw are removed by washing with pure water; Preferably, in step S1, the crop straw is dried at 40-80°C; Preferably, in step S1, the screening is performed by filtering through a 30-50 mesh screen; Preferably, in step S1, the crop straw includes any one or more of wheat straw, corn straw, rice straw, and cotton straw.
3. The method according to claim 1, characterized in that In step S2, the diameters of the spherical zirconia are 4-7 mm and 8-12 mm, the weight ratio of the two diameters is (3-5):1, and the mass ratio of the spherical zirconia to the crop straw is (50-150):1; Preferably, the mass ratio of spherical zirconium oxide to crop straw is 100:1; Preferably, in step S2, the straw powder is placed in a ball mill container and then ground at a speed of 300-500 rpm / min for 3-8 hours, with the rotation direction being changed every 0.5-1 hour.
4. The method according to claim 1, characterized in that In step S3, the mass volume ratio of the mixed solution of B-Straw powder, metal compound and Zn(NO3)2·6H2O is (1-10): 500 g / mL; In the mixed solution of the metal compound and Zn(NO3)2·6H2O, the concentration of the metal compound is 10-50 mM, and the concentration of Zn(NO3)2·6H2O is 50-200 mM; The mixture is allowed to stand for aging for 5-24 hours; the precursor is separated by suction filtration and dried at 40-80°C.
5. The method according to claim 1, characterized in that In step S4, the precursor is uniformly mixed with 8-12 times the weight of the nitrogen source; Preferably, in step S4, the precursor and the nitrogen source are uniformly mixed by grinding; Preferably, in step S4, the mixed powder is annealed in a tube furnace under a nitrogen atmosphere at a flow rate of 10-100 mL / min; Preferably, in step S4, the mixed powder is annealed in a nitrogen atmosphere at a flow rate of 40-60 mL / min, the temperature is increased from room temperature to 500-600°C at a rate of 5°C / min, and the temperature is kept constant for 1-2 hours, and then the temperature is increased to 850-950°C at a rate of 3°C / min, and the temperature is kept constant for 1-2 hours.
6. The method according to claim 1, characterized in that In step S5, the product obtained in S4 is washed with hydrochloric acid and then dried, and then ground and sieved to obtain a nitrogen-doped metal nanocluster ball-milled straw biochar catalyst; Preferably, the hydrochloric acid concentration is 0.5-2 mol / L, and after stirring and soaking for 2-6 hours, it is washed with pure water until it becomes neutral; After grinding, pass through a 50-200 mesh sieve.
7. A nitrogen-doped metal nanocluster ball-milled straw biochar catalyst, characterized in that: Prepared according to the method according to any one of claims 1 to 6.
8. Use of the nitrogen-doped metal nanocluster ball-milled straw biochar catalyst prepared by the method according to any one of claims 1 to 6 in the oxidative degradation of organic pollutants in wastewater treatment.
9. The use according to claim 8, characterized in that Application of the nitrogen-doped metal nanocluster ball-milled straw biochar catalyst prepared by the method according to any one of claims 1 to 6 in catalytic oxidant degradation of organic pollutants in wastewater; Preferably, the oxidant includes one or more of sodium persulfate, potassium persulfate, potassium hydrogen persulfate, sodium peroxydisulfate, and potassium periodate; Preferably, the organic pollutants include one or more of p-nitrophenol, bisphenol A, oxytetracycline, ciprofloxacin, and phenytoin.
10. The use according to claim 8, characterized in that The specific method of the application comprises the following steps: Put nitrogen-doped metal nanocluster ball-milled straw biochar catalyst and one or more of sodium persulfate, potassium persulfate, potassium hydrogen persulfate, sodium peroxydisulfate, and potassium periodate into wastewater containing organic pollutants at a pH of 3.8-10 and after deep treatment at a temperature of 15-40°C, and stir continuously until the organic pollutants are degraded; Preferably, the deep treatment method for the wastewater is a deep defluorination treatment process for low-concentration fluorine-containing wastewater.
Citation Information
Patent Citations
Low-concentration fluorine-containing wastewater deep fluorine removal treatment technology and fluorine removal treatment system
CN110407368A